Identifying Water Oxidation Mechanisms at Pure and Titanium‐Doped Hematite‐Based Photoanodes with Spectroelectrochemistry. Issue 12 (5th November 2021) - Zhang, Jifang; Lin, Qiyuan; Wang, Zhenlei; Liu, Haowen; Li, Xuanzhang; Zhang, Yuegang
Abstract: Investigation of the mechanism of the water oxidation reaction for hematite photoanodes has been one of the most persistently pursued topics in the course of understanding photoelectrochemical water splitting by transition metal oxides. Unfortunately, existing experimental techniques often require over‐simplified models and theories that assume only one reaction path. In this work, however, it is proposed that water oxidation on hematite can proceed via mixed reaction paths according to spectroelectrochemical results without a priori assumptions. The true absorption signals of surface states responsible for water oxidation are isolated from subsidiary signals for undoped and Ti‐doped hematite and contrasted with those of inactive species. The evolution of absorption signals as a function of applied potential and illumination intensity highlights the non‐negligible contribution of direct hole transfer, especially for highly doped hematite. Abstract : This work demonstrates a spectroelectrochemical methodology to identify the surface species, both active and inactive, for water oxidation reaction and also reveals the important roles of direct valence band hole transfer for hematite photanodes. Titanium doping not only improves electron transport but also reconstructs the electrode surface for more efficient solar water oxidation.